ARDUINO BASED WIRELESS MOBOT - A, Vishwanathraddi; Chakravarthi, M Kalyan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Increased connectivity and remote monitoring and control mechanisms have revolutionized the field of measurement and automation. The proposedÂ work is to design a system which will integrate a mobile bot with Arduino, and it is also possible with LabVIEW through a gateway to run wirelessly. AnÂ autonomous robot vehicle is to travel from source to destination through the wheels which are controlled by processor. This will be helpful launch inÂ the application where human being travel will be difficult to meet the work. The proposed system will be able to follow a path with obstacle avoiding.Further, the vehicle can be integrated with NI instruments and with LabVIEW to make it autonomous. LabVIEW is a graphical programming languageÂ gives a platform for the engineers, which is effective and scalable to focus on robotics neglecting the minute implementation details. Â